Listening Skills: Accountancy Educators in Retreat? - Alan Reddrop; Gido Mapunda (Australasian Accounting, Business and Finance Journal, 2019)
Purpose: to gain insight into the training received by accountancy graduates in soft skills with a major focus on listening skills; and, both, in light of findings, and impelled by the pleas of accountants’ clients, to urge educators to introduce them in curricula. Approach: content analysis of Australian accountancy schools’ courses placed on the web followed by direct contact with schools whose Web descriptions might plausibly have indicated listening skills’ inclusion; Findings: while the Institute of Chartered Accountants in Australia and CPA Australia required in their Professional Accounting Guidelines, 2009’ that as a condition of their accreditation higher education programs address ‘generic skills’ including the interpersonal, ‘particularly the ability to listen effectively’, this was scarcely complied with by accredited schools . Subsequent to the 2009 ICAA/CPA directive successive pronouncements of the Institutions reduced or effectively eliminated the requirement to teach listening skills. Practical implications: accountancy graduates will enter the profession without groundwork in a skill which successful exponents will increasingly be required to exercise. This will need to be remedied. Originality value: empathetic listening skills are seen to be indispensable by reference to the demands of a party not considered in previous studies, namely practising accountants’ clients. Nor have previous studies adequately recognised the critical importance of these skills as artificial intelligence (AI) erodes accountants’ standing as dispensers of technical knowledge.
Keywords: Listening skills; accountants’ clients’ needs; accountancy educators; artificial intelligence.